Automação de projetos de estruturas metálicas em plataforma CAD - Alexandre Caram e Silva (2008)
This paper deals with techniques of Object Oriented Programming (OOP) applied to the development of routines that offer automation in the execution of the process of steel structures projects. The main purpose of this project is the automation of phases of the process, basically combining the levels related to the analysis, dimensioning, and designof steel structures. The system was developed using the OOP paradigm which allows a user-friendly interface to automatize data gathering from structural analysis to perform the dimensiong of an I profile and its rigid connection with a column, according to the new ABNT (Associaçao Brasileira de Nomas Técnicas) NBR 8800. The AutoCAD programming environment has been chosen because of its great acceptance into the structural design offices. The automation of the mentioned phases of the process using CAD/CAE technologies was achieved with the development of a computer system, where dynamic libraries classes were created as AutoCAD Plug-ins. The interface between the CAD/CAE systems were developed through an API (Application Program Interface) called ObjectARX (Autocad Runtime eXtension). The phases in the process are automatized using parameters passed through the ASCII text files format, in order to assure a structural design completely safe and reliable. Due to the reusability and modularity of the code, developed in Object Oriented Programming, dimensioning and desinging new other profile can easily be created and incorporated to the system with no major problems.